Deskripsi tipe pertanyaan siswa berdasarkan sifatnya pada kegiatan menanya dalam pembelajaran matematika dengan pendekatan saintifik - Sudarmanti Sudarmanti; Supriyono Supriyono; Mujiyem Sapti; Abdul Rochim (Jurnal Inovasi Pendidikan Matematika (JIPM), 2020)
The purpose of this research to describe the type of student question on learning mathematics with a scientific approach. This research at the tenth-grade student of SMA Negeri 7 Purworejo in the academic year of 2019/2020. The design of the study used descriptive quantitative. This research uses purposive sampling. The research took 36 students of X MIA 6. The researchers analyzed the data by using observation, video records, and field notes. The result of the study show that the type of question many student convey a remember information, concept understanding and concept applying in learning material